Quantitative and qualitative composition of proanthocyanidins and other polyphenols in commercial red wines and their contribution to sensorially evaluated tannicity - Laitila, Juuso Erik (Elsevier Ltd, 2025)
The analysis of proanthocyanidins (PA) in red wine has typically been conducted using few key methods, such as phloroglucinolysis or precipitation assays. Here, the content of PAs and other common polyphenol groups in commercial red wines were analyzed with a group-specific liquid chromatography-tandem mass spectrometry method. Besides concentrations, the method provides qualitative information about the detected compound groups in the form of two-dimensional (2D) chromatographic fingerprints. The 2D fingerprints of PAs have not been utilized in analysis of red wine before. For instance, 2D chromatographic fingerprints revealed that the complex PA compositions were qualitatively notably similar between many wine types, even when there were considerable differences in concentrations. Finally, 201 commercial red wines had been categorized as either tannic or medium tannic based on their sensorial evaluations. The content of PAs and three different groups of oligomeric adducts of malvidin glycosides and PAs were measured from these wines. The compositional features of the PAs and PA-malvidin glycoside adducts were more important than concentrations in explaining the perceived tannicity.